DETERMINING PARAMETERS OF DIPROPINATE RESIDUES IN COW MILK AFTER APPLICATION OF IMKAR-120 THERAPEUTIC DOSES - Levytska, V. A.; Berezovsky, A. V.; Mushynskyi, A. B. (Scientific Progress & Innovations, 2020)
Bovine babesiosis is an acute, often enzootic, tick-borne disease characterized by fever, anemia, icteric discoloration of the mucous membranes, hemoglobinuria, digestive disorders, and a sharp decrease in milk yield of dairy cows. Imidocarb is considered one of the most effective and safest of all available medicines for parasitic blood diseases. The aim of our study was to determine the amounts and timing of imidocarb excretion with milk in lactating cows. Milk sampling for the preparation testing was carried out in early June of 2020 from five cows from the herd of a private farmer in the village of Slobidka-Kulchiievetska, Ka-myanets-Podilsky district, Khmelnytsky region, after the cows were diagnosed with babesiosis and treated with Imkar-120 at a dose of 2 ml per 100 kg of body weight, once, subcutaneously. At the same time, the rest of the cows in the herd was administered this preparation for prophylactic purposes in the same dose. On the first and second days after medicine administration, milk samples were taken twice, and on the third or tenth day, once – during the evening milking. From the milk samples of each cow, 50 ml of milk were taken and one pool sample (250 ml) was formed for investigation. As a result of cow milk studies it was established that during the first day after injection, the level of imidocarb concentration in the pool sample was 560 μg/kg and it gradually decreased over ten days. Pool milk samples contained the residues (46 μg/kg) of imidocarb on the 4 th day. The sample analysis during the next six days of our studies showed that the level of the prep-aration active substances gradually decreased daily from 39 to11 μg/kg. According to the established stand-ards for Ukraine, milk containing 50 μg (or less) of imidocarb in 1 kg of milk is allowed for sale. Taking into account the fact that imidocarb dipropionate, the active basis of Imkar-120 Ukrainian generic preparation, is excreted with milk in terms, which coincide with similar medicines of European manufacturers, it can be recommended for the treatment of lactating cows diseased with babesiosis and anaplasmosis.